Impact of Gas Delivery Systems on Imaging Studies of Human Cerebral Blood Flow. (11th December 2013) - Cain, John R.; Parkes, Laura M.; Eadsforth, Peter; Beards, Susan C.; Jackson, Alan
Abstract : Purpose . To compare a semiopen breathing circuit with a non-rebreathing (Hudson mask) for MRI experiments involving gas delivery. Methods and Materials . Cerebral blood flow (CBF) was measured by quantitative phase contrast angiography of the internal carotid and basilar arteries in 18 volunteers (20–31 years). In 8 subjects, gases were delivered via a standard non-rebreathing (Hudson mask). In 10 subjects, gases were delivered using a modified "Mapleson A" semiopen anesthetic gas circuit and mouthpiece. All subjects were given 100% O2, medical air, and carbogen gas (95% O2 and 5% CO2 ) delivered at 15 L/min in a random order. Results . The Hudson mask group showed significant increases in CBF in response to increased FiCO2 compared to air (+9.8%). A small nonsignificant reduction in CBF (−2.4%) was seen in response to increased inspired concentrations of oxygen (FiO2 ). The Mapleson A group showed significantly larger changes in CBF in response to both increased inspired concentrations of carbon dioxide (FiCO2 ) (+32.2%, P < 0.05 ) and FiO2 (−14.6%, P < 0.01 ). Conclusions . The use of an anaesthetic gas delivery circuit avoids entrainment of room air and rebreathing effects that may otherwise adversely affect the experimental results.